Growth, Chl a content, photosynthesis, and elemental composition in polar and temperate microalgae. (10th October 2016) - Lacour, Thomas; Larivière, Jade; Babin, Marcel
Abstract: Polar microalgae live under extreme environmental conditions: permanently low temperatures (−1.7°C to +5°C) and extreme variations in irradiance and day length. These conditions may have led to various specific adaptations allowing Arctic phytoplankton to become specialists under these conditions. The goal of this study is to derive, for polar microalgae, empirical relationships between key physiological parameters (growth rate, photosynthesis–irradiance curve parameters, Chl a  : C, and N : C ratios) and growth temperature and irradiance in nutrient replete cultures. Ecophysiological characteristics of polar and temperate microalgae were also compared in order to highlight some strategies that are specific to the polar environment. Most of the polar species are psychrophilic. Polar microalgae have low light‐saturated growth rates (μm ) and very low light saturation parameters for growth ( K E ) but similar initial slopes of their growth–irradiance curve ( α µ  = μm / K E ). Low temperatures probably account for low μm and K E in polar species. The C : Chl a ratios ( θ ) of polar species are similar to those of temperate species although they have much lower growth rates, which implies major differences in energy allocation. Polar microalgae also exhibit very unique photosynthetic properties [low light saturation parameters for photosynthesis ( E K ), low maximum photosynthetic rates ( P m C ), decreasing P m C and decreasing initial slope of the photosynthesis vs. irradiance curve ( α *) with increasing irradiance] and have lower C : N ratios than their temperate cousins, which may be related to a much higher protein content. Some of the implications of these findings in terms of adaptation/acclimation to the environment in which polar species evolve are discussed.